Successful probing of Congenital Nasolacrimal Duct Obstruction on 11 years old child: A case report: Poster Presentation - Case Report - Ophthalmologist - SUTJIPTO; Mohammad Haikal Bakry (Majalah Oftalmologi Indonesia, 2023)
Introduction : Congenital nasolacrimal duct obstruction (CNLDO) is a common cause of epiphora in infants; its prevalence rate of 5% to 20%, although only 2–6% will need intervention. The pathogenesis involves an imperforate membrane of the nasolacrimal duct but it may involve bony abnormalities and narrowing of the lacrimal drainage system. Case Illustration : An 11-year-old boy came to the hospital with complaints of a watery and excreted eye since he was born. On the dye disappearance test the result is +4. The patient was decided to have probing procedures. There was positive dye flow in the nasolacrimal duct after probing and irrigation with saline and dye. One week after the probing procedure, dye disappearance test was performed and the result is negative. Patients also no longer complain of watery and sticky eyes. Discussion : The management of CNLDO remains controversial. Probing can be used as a primary treatment for children <36 months of age, where success rate of 78–93% can be achieved. For older children success rate is even less. Studies on older children between 25 and 60 months have shown failure rates as high as 28%. The prevalence of complex obstruction in children between 49 and 60 months was 43% with a success rate of only 33% on probing. Conclusion : Appropriate time for probing the CNLDO is still under debate. The high success rate of probing in patients older than 2 years old confirm that the first intervention could be probing before considering complex intervention.